From Cultural Heritage to Classroom: Adapting the Panji Laras Mask Dance for Psychomotor and Socio-Emotional Development in Kindergarten - Wulandari, Retno Tri; Jazuli, Muhammad; Cahyono, Agus; Hidajat, Robby (Journal of Cultural Analysis and Social Change, 2026)
Traditional performing arts have rarely been embedded in early childhood curricula despite their developmental and cultural potential. This study adapted the Panji Laras Mask Dance for kindergarten learners in Malang, Indonesia, to address that gap. Using a descriptive qualitative single-case design, the research involved collaborative workshops with teachers and cultural practitioners, twelve classroom observations, in-depth interviews, and document analysis. Developmental assessments were used descriptively to support qualitative interpretation. Data analysis employed content analysis with iterative verification, and expert validation was obtained through a focus group with Malang mask dance artists and scholars. Findings demonstrated clear gains in psychomotor coordination steadier rhythm, more controlled sequencing, and improved spatial awareness as well as marked socio-emotional growth reflected in sustained engagement, cooperative turn-taking, and increased performance confidence. Teachers reported easier instruction and clearer gesture–meaning links, while cultural practitioners confirmed that symbolic intent remained legible after simplification. As a curricular value, the adaptation provided a coherent package of character-oriented learning objectives, movement-with-meaning materials that connect Panji symbols to embodied experience, and performance-based assessment rubrics that could be operationalized in class. This curricular contribution aligned with Indonesia’s Pancasila Student Profile (P5) projects and offered implementable tools such as session plans, performance indicators, and observation rubrics for replication across kindergartens. Thus, Panji Laras proved to be not only teachable but also curricularly valuable, offering a measurable pathway to integrate culture and character at developmentally appropriate levels.